DIESEL ENGINE EMISSIONS IMPROVEMENTS BY THE USE OF SUN FLOWER METHYL ESTER/DIESEL BLENDS - (:unkn) unknown (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2013)
The study focuses on the influence of blending sun flower methyl ester (SOME) to conventional diesel. In order to determine the emission characteristics of SOME/diesel blends, the engine was performed at five different engine speed under full load condition. With addition of SOME resulted in a combined increase in smoke opacity, CO2 and NOX emissions and decrease in CO and HC emissions. Also, BSFC of SOME is close to the values obtained from diesel fuel. Hence, it has been seen that blend of SOME and diesel fuel can be used as alternative fuel successfully in a diesel engine without any modification and also it is an environmental friendly fuel in terms of emission parameters.
Keywords: Diesel engine; Sun flowermethyl ester; Specificfuelconsumption; Exhaustemissions; BIODIESEL PRODUCTION; OIL; EXHAUST; FUEL; PERFORMANCE